2002
DOI: 10.1152/physiolgenomics.00106.2001
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen M235T polymorphism associates with exercise hemodynamics in postmenopausal women

Abstract: .-We sought to determine whether the M235T angiotensinogen (AGT) polymorphism, either interacting with habitual physical activity (PA) levels or independently, was associated with cardiovascular (CV) hemodynamics during maximal and submaximal exercise. Sixty-one healthy postmenopausal women (16 sedentary, 21 physically active, and 24 endurance athletes) had heart rate (HR), blood pressure (BP), cardiac output, stroke volume (SV), total peripheral resistance (TPR), and arteriovenous O 2 difference (a-vDO2) asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Using the same women tested as in the present study, we have found other genes that were associated with HR during submaximal and maximal exercise [13,14,26]. McCole et al showed that the common angiotensinogen M235T polymorphism had a significant effect on submaximal and maximal exercise HR.…”
Section: Discussionsupporting
confidence: 57%
“…Using the same women tested as in the present study, we have found other genes that were associated with HR during submaximal and maximal exercise [13,14,26]. McCole et al showed that the common angiotensinogen M235T polymorphism had a significant effect on submaximal and maximal exercise HR.…”
Section: Discussionsupporting
confidence: 57%
“…The M235T missense polymorphism in the angiotensinogen gene AGT showed a positive association with several measures of cardiorespiratory performance in 61 healthy postmenopausal women, including 24 elite endurance athletes (McCole et al 2002), and with left ventricular mass (LVM) in two separate studies on elite endurance athletes: a highly significant association in a cohort of 50 male and 30 female athletes (Karjalainen et al 1999) and a weak association in a combined analysis with genotype at the ACE I/D polymorphism in 83 male athletes (Diet et al 2001). No evidence of an association was identified in two cohorts of untrained individuals (Linhart et al 2000;Kauma et al 1998).…”
Section: Genetic Associations With Performance-related Traitsmentioning
confidence: 96%
“…[32][33][34][35][36][37][38][39][40] Some, but not all, of these studies emanate from clinical trials of exercise, diet or drug treatment interventions on blood pressure regulation. The most widely studied gene in this context is the angiotensinogen I-converting enzyme gene (ACE).…”
Section: Gene-environment Interactionmentioning
confidence: 99%
“…Studies examining the modifying roles of ACE genotypes on blood pressure response to exercise have focused primarily on the effects of acute exercise often in relatively small samples. [32][33][34][35][36][37][38][39] At least two medium-to long-term clinical trials from North America 37 and Finland 40 have reported on the association between ACE genotypes and blood pressure responses to long-term aerobic exercise training. In the North American HERITAGE study, Rankinen and colleagues examined the blood pressure response by ACE I/D and M235T genotypes to an exercise stress test before and after 20 weeks of aerobic exercise training.…”
Section: Gene-environment Interactionmentioning
confidence: 99%